SOLUSI PERMASALAHAN KESEHATAN DENGAN PENGAMALAN AL-QUR’AN DAN SUNNAH RASULULLAH SAW - Siti Mariyam; Deti Indah Kiranti; Devi Oktavini; Ismaya Febrianti; Hisny Fajrussalam (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2022)
Health is something that is the hope of all creatures on this earth. Carrying out all activities such as worshiping, working, eating, drinking, and so on requires physical and psychological health to support the success of each activity carried out. The research was conducted to determine the extent to which the public understands the importance of health, as well as the appropriate solutions to overcome health problems that often occur in the community. Questionnaires were distributed with the target of 34 students, college students, and the general public using qualitative methods in the form of resource persons' answers which were then processed so as to obtain accurate results related to the research carried out. Here we describe several matters relating to the solution of health problems, including the Islamic view on health, healthy living behavior based on the sunnah of the Prophet S.A.W. the role of the Qur'an in terms of health, as well as explaining how its implementation in realizing healthy living behavior. The results of the research show that the Qur'an and the Sunnah of the Prophet S.A.W. very influential for the solution of physical and psychological health problems for the community, including those who feel calm and happiness when practicing the sunnahs of the Prophet S.A.W., and feel physical and mental health and comfort in carrying out daily activities. The practices of the Prophet S.A.W. Of course, it has a positive impact on people's lives if they are able to implement it, especially for health problems. The amount of information obtained is able to explain how the position of the Qur'an and the Sunnah of the Prophet S.A.W. proven to be the best solution in overcoming public health problems. Thus, deepening religious knowledge, reading books and various other sources, as well as natural tadabbur can increase knowledge related to this matter.